Nonintubated thoracoscopic anatomical segmentectomy for lung cancer: a single-center experience with consecutive 89 cases - Hung, Ming-Hui; Wang, Man-Ling; Cheng, Ya-Jung; Hsu, Hsao-Hsun; Chen, Jin-Shing (Video-Assisted Thoracic Surgery, 2017)
Background: Recent development in minimally invasive thoracic surgery for lung cancer includes a combination of nonintubated anesthetic management and sublobar resection in patients with compromised cardiopulmonary function or with early-stage lung cancer. Methods: From August 2009 to December 2016, 89 patients with lung cancer underwent thoracoscopic anatomical segmentectomy without endotracheal intubation, using a combination of thoracic regional anesthesia and targeted sedation during surgery. Results: There were 28 patients (31%) undergoing compromised nonintubated thoracoscopic anatomical segmentectomy due to advanced age or poor lung function reserve. Left upper apical trisegmentectomy was most commonly performed (n=21), followed by left upper lingulectomy (n=16) and right upper superior segmentectomy (n=15). Conversion to intubated general anesthesia was required in two patients because of vigorous mediastinal movement. No patient required conversion to a thoracotomy or lobectomy. Prolonged chest tube drainage was noted in three patients who had air leak (n=2) or chylothorax (n=1). The median chest drainage and hospital stay were 2 and 4 days, respectively. The median time of anesthetic induction and operation were 15 and 135 minutes, respectively. Conclusions: Nonintubated thoracoscopic anatomical segmentectomy is safe and technically feasible using regional thoracic anesthesia and conscious sedation. In selective lung cancer patients, a less invasive nonintubated thoracoscopic segmentectomy can be an alternative to intubated one-lung ventilation or to a complete lobectomy.